Scientometric Portrait of Nobel Laureate John F Clauser - Hakkaraki, Vinayak Parashuram (Journal of Data Science, Informetrics, and Citation Studies)
American experimental physicist John Francis Clauser is renowned for his contributions to the foundations of quantum mechanics, in particular the Clauser-Horne-Shimony-Holt inequality. Along with Alain Aspect and Anton Zeilinger, John F Clauser received the Physics Nobel Prize in 2022 "for experiments with entangled photons, establishing the violation of Bell inequalities, and pioneering quantum information science". The current study's goal was to look into and evaluate various facets of the research publications of Nobel Prize-winning scientist John F. Clauser. Fundamental Scientometric criteria, such as publication growth patterns, authorship status, most active collaborators, and core journals preferred for publications, were used to evaluate his publications. The Dimensions AI database was used to analyse the publications and citations of the data. Between 1966 and 2023, the John Francis Clauser bibliographic analysis turned up 55 articles. This study looks at a number of factors, including citation, document type, author models, core journals preferred for publications, etc.
Keywords: Scientometric Portrait; Bio bibliometric; Publication productivity; Citations; Scientist; John Francis Clauser; Nobel Prize.